Global Perspectives on NGO Communication for Social Change - Sorce, Giuliana (Routledge Research in Communication Studies, 2022)
This book examines the central role media and communication play in the activities of Non-Governmental Organizations (NGOs) around the globe, how NGOs communicate with key publics, engage stakeholders, target political actors, enable input from civil society, and create participatory opportunities. An international line-up of authors first discuss communication practices, strategies, and media uses by NGOs, providing insights into the specifics of NGO programs for social change goals and reveal particular sets of tactics NGOs commonly employ. The book then presents a set of case studies of NGO organizing from all over the world-ranging from Sudan via Brazil to China - to illustrate the particular contexts that make NGO advocacy necessary, while also highlighting successful initiatives to illuminate the important spaces NGOs occupy in civil society. This comprehensive and wide-ranging exploration of global NGO communication will be of great interest to scholars across communication studies, media studies, public relations, organizational studies, political science, and development studies, while offering accessible pieces for practitioners and organizers.